(untitled) (Teaching and Learning Inquiry, 2021)
Mentoring relationships that form between scholars of teaching and learning occur formally and informally, across varied pathways and programs. In order to better understand such relationships, this paper proposes an adapted version of a three-stage model of mentoring, using three examples of unseen opportunities for mentoring in the Scholarship of Teaching and Learning (SoTL) to illustrate how this framework might be operationalized. We discuss how the adapted framework might be useful to SoTL scholars in the future to examine mentorship and how unseen opportunities for mentoring might shape how we consider this subset of mentorship going forward.